Legal Effects of the Constitutional Court's Ruling Against Marital Agreement in Mixed Marriages - Maulidia Mulyani (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2022)
Abstract: Prior to the issuance of the Constitutional Court (MK) decision Number 69/PUU-XIII/2015, some mixed-marriage couples complained about the state policy that does not allow mixed-marriage couples to own assets, both in the form of building use rights (HGB) and business use rights (HGU). This article examines a marriage agreement made by a mixed marriage couple, namely Indonesian and foreign couples after the Constitutional Court decision Number 69/PUU-XIII/2015. Two fundamental issues are the focus of this article, namely how is the legal impact of the Constitutional Court Decision Number 69/PUU-XIII/2015 on marriage agreements in mixed marriages, and what are the legal consequences of the Constitutional Court Decision? The following findings were obtained using a juridical-normative approach and utilizing Gustav Radburch's theory of the legal purpose: first, after the Constitutional Court decision the perpetrators of mixed marriages had a looser time to make a marriage agreement. They can agree before the marriage contract or during the marriage bond. Second, a marriage agreement made during the marriage period will be valid the moment after it is made, and the separation of the joint property of both parties can immediately follow it. Third, when viewed from the theory of Gustav Radburch's legal objectives, the Constitutional Court Decision has fulfilled the purpose of making law: the realization of justice, certainty, and legal expediency. However, on the other hand, the Constitutional Court ruling has also put third parties in a vulnerable position.Abstrak: Sebelum terbitnya putusan Mahkamah Konstitusi (MK) Nomor 69/PUU-XIII/2015, beberapa pasangan perkawinan campuran mengeluhkan kebijakan negara yang tidak memperbolehkan pasangan perkawinan campuran untuk memiliki aset, baik berupa hak guna bangunan (HGB) maupun hak guna usaha (HGU). Artikel ini mengkaji sebuah perjanjian perkawinan yang dilakukan oleh pasangan perkawinan campuran, yaitu pasangan WNI dan WNA pasca Putusan Mahkamah Konstitusi (MK) Nomor 69/PUU-XIII/2015. Ada dua persoalan mendasar yang menjadi fokus artikel ini, yakni bagaimana dampak hukum yang ditimbulkan dari adanya Putusan Mahkamah Konstitusi Nomor 69/PUU-XIII/2015 terhadap perjanjian perkawinan dalam perkawinan campuran, dan bagaimana dampak hukum Putusan MK tersebut? Menggunakan pendekatan yuridis-normatif dan memanfaatkan teori tujuan hukum Gustav Radburch diperoleh temuan sebagai berikut: pertama, pasca Putusan MK Nomor 69/PUU-XIII/2015, para pelaku perkawinan campuran memiliki waktu yang lebih longgar untuk membuat perjanjian perkawinan. Mereka bisa membuat perjanjian sebelum dilakukannya akad perkawinan ataupun selama dalam ikatan perkawinan. Kedua, perjanjian perkawinan yang dibuat dalam masa perkawinan akan berlaku sah pada saat setelah dibuat, dan hal itu bisa langsung diikuti dengan pemisahan harta bersama kedua belah pihak. Ketiga, jika dilihat dari teori tujuan hukum Gustav Radburch maka Putusan MK tersebut telah memenuhi tujuan dibuatnya hukum, yakni terwujudnya keadilan, kepastian, dan kemanfaatan hukum. Akan tetapi, di sisi lain, Putusan MK tersebut, juga telah menjadikan pihak ketiga berada dalam posisi rentan.Keyword: Constitutional Court Decision; legal effect: marriage agreement; mixed marriage.